(untitled) - The World Bank in Vietnam (WB) (Hà Nội, 2003)
The Urban Transport Improvement Project's overall objective is to increase operational efficiency and safety of selected corridors and in the central areas of Hanoi and Ho Chi Minh City (HCMC). The specific goals are to: a) increase the capacity and improve operating conditions of major road corridors, central areas and strategic intersections by introducing traffic management and engineering measures; and b) strengthen the institutional capacity in traffic management and traffic enforcement. The project consists of two main components. The first component will involve improving traffic system on four main radial corridors and in two inner city areas in Hanoi City. It will also improve junctions and channelization and provide railway barriers at the junctions. The second component will improve the traffic system on four major corridors, at 14 isolated junctions and within the central area in HCMC. A fully responsive area traffic control system covering about 150 intersections will also be implemented in central HCMC. In both components, technical assistance, training, and equipment will be provided for institutional strengthening.
Keywords: Urban transportation,Giao thông đô thị; Vietnam,Việt Nam